Factors Influencing Audit Expense and Quality in an Emerging Economy: A Study on Bangladesh - Ahmed, Tanvir; Hera, Shehrly Mahboob; Rimi, Tasmima Jannat; Hassan, Tanvir (The Economics and Finance Letters, 2020)
This determination of this study to find the association between audit expense, and the significance of the relationship in an emerging economy. Whereas, audit quality is associated with audit expense of a company. The regression model used here taken from (Simunic, 1980). This study is based on five different hypothesis. Descriptive statistics, multiple linear regression, correlation analyses are used for describing the results. For reflecting the proper findings, 23 companies from IT, cement and ceramic sectors are chosen here as sample. Some companies are taken from miscellaneous companies from Dhaka Stock Exchange (DSE). The findings imitates that audit expense is highly dependent on the company size, accounting firm’s type, equity-debt ratio. Company size and accounting firm’s type are positively significant where equity-debt ratio is negatively significant. Whereas, audit expense also depends on the date of report making. Therefore, big companies need to be concerned about their audit quality, as audit quality could be hampered because of overgenerous compensation. Practical. This outcome will help the stakeholders of the company to judge about the reason of fluctuating audit expense, and probable recommendation as well. Value-The originality of this study to define the fluctuations of audit expense in diverse ways, and find the probable reason of the fluctuations. This paper will help stakeholders to find the probable causes of fluctuating audit quality.